<span>A polynomial with the given zeros can be represented as
f(x) = (x-1)(x-2)(x+2)(x+3).
Note that if you set f(x) = 0, then 1,2,-2, and -3 certainly are the solutions. From here, we simply multiply/expand out the polynomial. We can do this in a variety of ways, one of which is taking the left two and right two products separately. We have
(x-1)(x-2) = x^2 - 3x + 2
and
(x+2)(x+3) = x^2 + 5x + 6.
This gives that
f(x) = (x^2 - 3x + 2) (x^2 + 5x + 6).
Expanding this expression out then gives us our answer as
f(x) = x^4 + 2x^3 - 7x^2 - 8x + 12
or answer choice B.</span>
Answer:
(6,-3) or x=6 y= -3
Step-by-step explanation:
Answer:
$1.00
Step-by-step explanation:
Answer:
A 3x^12 - 2x^8 + x^5
Step-by-step explanation:
Degree of a polynomial:
The degree of a polynomial is given by the highest exponent of x.
In this question:
Option A: 12th degree
Option B: 1st degree
Option C: 3rd degree
Option D: 3rd degree
So the answer is given by option A.